Estratégias competitivas utilizadas pelas concessionárias de veículos novos em São Luís/MA - Beserra, João Mauricio Carvalho (2010)
The objective is to analyze the competitive strategies used by new car dealerships in São Luiz. This research is justified by the importance of the automotive sector. This is an expanding sector, with growth in volume sales of new vehicles, increasing competition, and competitiveness which becomes more pronounced. Thus, the strategies used by the utilities become a major factor in their survival and differentiation in this type of market. The relationship between carmakers and dealers is another important point that influences the strategies of the utilities. This study is about a descriptive, quantitative, based on secondary data and primary data collected through field research, using a questionnaire applied in the authorized dealers of new vehicles in São Luiz / MA. The result showed that the automakers have strong influences in defining strategies of the utilities and they are seeking alternative ways to increase profitability, becoming centers of automotive services with the provision of differentiated services.